1992
DOI: 10.1016/0741-5214(92)90171-4
|View full text |Cite
|
Sign up to set email alerts
|

Modified polytetrafluoroethylene: Indium 111-labeled platelet deposition on carbon-lined and high-porosity polytetrafluoroethylene grafts

Abstract: Platelet accumulation on carbon-lined (CL) and high-porosity (Ill') polytetrafluoroethylene (PTFE) grafts was investigated in vivo. In experiment l, 20 CL grafts and 20 control PTFE grafts, each 5 cm in length and 4 mm in diameter, were interposed into both carotid and femoral arteries of 10 dogs. In experiment 2, 12 lip grafts (90 Itm mean internodal distance) and 12 control PTFE grafts were implanted in six dogs. Indium Ill-labeled platelets were injected intravenously and the grafts were retrieved 48 hours … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Carbon particles are permanently integrated into the ePTFE material and are uniformly distributed through 25% of the wall. Animal studies have demonstrated that compared with standard PTFE grafts, carbon lining significantly decreases platelet accumulation, 8 and deposition by a factor of six. 9…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbon particles are permanently integrated into the ePTFE material and are uniformly distributed through 25% of the wall. Animal studies have demonstrated that compared with standard PTFE grafts, carbon lining significantly decreases platelet accumulation, 8 and deposition by a factor of six. 9…”
Section: Methodsmentioning
confidence: 99%
“…1,3 Rheolytic thrombectomy using the AngioJet device (Possis Medical Inc, Minneapolis, MN, USA) and a specially designed catheter (AVX or DVX) was performed for graft occlusion followed by angioplasty (±stenting) of the anatomical lesion (arterial anastomosis, graft, venous outflow, draining or central veins) responsible for the thrombotic event. 8,9 Isolated angioplasty (±stenting) of the anatomical lesion (arterial anastomotis, intragraft, venous outflow, draining or central veins) was performed for failing grafts.…”
Section: Methodsmentioning
confidence: 99%
“…410 To a lesser extent, companies have attempted to reduce graft clotting by altering the luminal surface of the graft and to improve upon post-dialysis bleeding, and they have made attempts to alter the graft structure and materials. 11–16…”
Section: Introductionmentioning
confidence: 99%
“…Carbon coating has been shown to decrease the thrombogenicity of Dacron grafts in vitro and in vivo [7]. Experimental data reported excellent results with carbon-lined PTFE grafts in a dog model using both carotid and femoral arteries [7,8] in a limited number of animals [t0]. The in vivo technique for detection of deposition of platelets and the formation of thrombus on PTFE grafts was developed and quantitated with 11~Indium-labeled autologus platelets according to the method described by Dewanjee et al, and modified in our laboratory by location of platelet deposition from [9][10][11] the scintiphotos using gamma-camera.…”
Section: Introductionmentioning
confidence: 99%